Der Wert der Preise Valorisierungsdynamik in der deutschen Literaturpreislandschaft 1990-2019 - Maaß, Sarah (Königshausen & Neumann, 2022)
This book presents the results of a research project at the University of Duisburg-... DFG-funded research project at the University of Duisburg- Essen. It invites the reader to follow the development of the German literary development since 1990. The diversity of the prizes is as impressive as the complexity of their functions. In the development of new formats for awarding prizes and awarding practices shows how literary literary events into the cultural changes of contemporary society. contemporary society; the emergence of new prize profiles signals and promotes the acceptance of new genres (such as comics, blogs or nature writing) in the literary writing) in the literary field; special prizes strengthen new alliances between literary between literary values and social objectives such as inclusion or inclusion or ecology; they promote new types of texts, new types of authors, new types of authors, new places, themes and forms of literary and evaluation. The connecting points for more in-depth individual studies that This book offers a correspondingly large number of points of contact for in-depth individual studies.